WORKSHOP PENULISAN KARYA ILMIAH SEBAGAI UPAYA PENGEMBANGAN PROFESIONALISME GURU SMK - Wening, dkk, Sri (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2009)
AbstractThe objectives of community service activity through scientific writingworkshop for vocational high school (SMK) teachers are: 1) to increaseprofessionalism development of SMK teachers to fulfill promotion requirement;2) to increase capability of making and presentation scientific writingproduct; and 3) to produce scientific writing product that ready to publish.The activities of scientific writing workshop was done by 54 teachersof SMKN 2 Godean. Workshop activities were done by using method:1) discourse about scientific writing, scientific writing ethics, scientific writingtechnique, language in scientific writing, reference scanning throughinternet, making scientific writing, and self-editing technique; 2) discussionat every matter submitted, participant can dialogue and discuss with team;3) task to make scientific product which to obtain certificate requirement.Making of scientific product was conducted by tutorial.The community service activity through scientific writing workshopcan be concluded successfully. It can be showed from positive response ofparticipant from target of 65 participants can be realized become 54 participantsor 83% at workshop implementation. Besides that the teachers getsattachment of knowledge and skill in reference scanning through internetaccess. However, target of the many scientific product that ready to publishis unattainable because the teachers have not motivation to write scientificproduct and the many activities of teacher in school.Keywords: profesionalisme, teachers, workshop, and scientific writing